Anesthetic management of precise radiotherapy under apnea-like condition. Issue 3 (March 2021) - Zhang, Shilong; Zhao, Bin; Chen, Dongji; Qi, Ying; Ma, Youguo; Ma, Juan; Xie, Wenjuan; Guo, Haiyan
Objective: To study the safety and feasibility of implementation of precise radiotherapy with inducement of an apnea-like condition. Methods: Two patients with lung tumors underwent precise radiotherapy under an apnea-like condition. The apnea-like condition was induced 11 times between the two patients for tumor localization and treatment. The changes in the blood oxygen saturation, blood pressure, heart rate, and end-tidal carbon dioxide during the apnea-like periods were observed, and the incidence of adverse reactions was recorded. Results: The average apnea-like time was 6.2 minutes (range, 3–9 minutes), and the average radiotherapy time was 4.6 minutes (range, 1–7 minutes). The lowest blood oxygen saturation level was 97%, with a change of <1%. The heart rate and average arterial blood pressure increased during the apnea-like periods. Contact sores appeared on the patients' posterior pharyngeal wall after the first apnea-like period; no other adverse events occurred. Conclusion: Precise radiotherapy under an apnea-like condition is safe and feasible for patients with lung tumors.